2021
DOI: 10.1016/j.breast.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Low neighborhood socioeconomic status is associated with higher mortality and increased surgery utilization among metastatic breast cancer patients

Abstract: Purpose Low socioeconomic status (SES) is associated with advanced stage, lower-quality care, and higher mortality among breast cancer patients. The purpose of this study is to examine the association between neighborhood SES (nSES), surgical management, and disease-specific mortality in de novo metastatic breast cancer (MBC) patients in the Surveillance, Epidemiology, and End Results (SEER) Program. Methods MBC patients ages 18 to 85+ years diagnosed from 2010 through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…16 Previous analyses also have methodologic limitations associated with confounding between neighborhood and individual-level factors or their design independently assesses only these measures of disadvantage rather than their joint outcome. 15,17 Moreover, these studies predominantly use national cancer databases that have limited data on key variables, such as age (eg, only include individuals aged Ն65 years), SES (eg, do not include uninsured, Medicare-ineligible populations), and racial and ethnic diversity (eg, only 5% of patients are Hispanic) along with an inability to capture National Comprehensive Cancer Network (NCCN) guideline-concordant treatment. 18,19 To overcome these data and methodologic limitations, we sought to assess whether there is an association between a robust validated measure of neighborhood disadvantage (Area Deprivation Index [ADI]) and breast cancer-specific survival in a diverse sociodemographic and racial and ethnic population with individual-level sociodemographic, comorbidity, breast cancer risk factor, access to care, tumor, and NCCN guideline-concordant treatment information not available in national cancer databases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Previous analyses also have methodologic limitations associated with confounding between neighborhood and individual-level factors or their design independently assesses only these measures of disadvantage rather than their joint outcome. 15,17 Moreover, these studies predominantly use national cancer databases that have limited data on key variables, such as age (eg, only include individuals aged Ն65 years), SES (eg, do not include uninsured, Medicare-ineligible populations), and racial and ethnic diversity (eg, only 5% of patients are Hispanic) along with an inability to capture National Comprehensive Cancer Network (NCCN) guideline-concordant treatment. 18,19 To overcome these data and methodologic limitations, we sought to assess whether there is an association between a robust validated measure of neighborhood disadvantage (Area Deprivation Index [ADI]) and breast cancer-specific survival in a diverse sociodemographic and racial and ethnic population with individual-level sociodemographic, comorbidity, breast cancer risk factor, access to care, tumor, and NCCN guideline-concordant treatment information not available in national cancer databases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found associations between neighborhood-level measures, such as socioeconomic status (SES), with disparities in breast cancer survival . However, many measures of neighborhood SES previously used do not encapsulate the various domains and complexities that contribute to neighborhood disadvantage .…”
Section: Introductionmentioning
confidence: 99%
“…in patients from low SES areas may limit access to institutions that are more likely to follow the most current guidelines. 54 The results from our study highlight the need for additional research elucidating the pathways between nSES and surgical management. Specifically, qualitative analytical tools such as intersectionality--describes the impact of multiple social identities (e.g., Black race, female gender, and class) on discrimination and disadvantage, provide a much needed contextual framework.…”
Section: Low Value Surgical Carementioning
confidence: 65%
“…Similarly, the interplay of multiple social determinants of health (transportation, personal finances, workplace flexibility, stress, etc.) in patients from low SES areas may limit access to institutions that are more likely to follow the most current guidelines 54 . The results from our study highlight the need for additional research elucidating the pathways between nSES and surgical management.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study noted that, when accounting for neighborhood socioeconomic status, Black women were more likely to adhere to endocrine therapy compared with White women . In women with metastatic breast cancer, neighborhood socioeconomic status rather than race was associated with the probability of receiving surgery . In the present study, ADI, which is a measure of neighborhood socioeconomic status, was not associated with either preferred or received surgery.…”
Section: Discussionmentioning
confidence: 92%